1981
DOI: 10.1017/s0021859600066284
|View full text |Cite
|
Sign up to set email alerts
|

Effect of adding water to paspalum (Paspalum dilatatum) hay on the feed intake of sheep

Abstract: Low quality roughages are a major feed resource for ruminants in Australia and many other parts of the world. Factors limiting the intake of these roughages include their high cell wall component and low crude protein content. Palatability may also be important. Low quality roughages are frequently dusty. Hence, the present experiment was initiated to determine whether water would affect the intake of paspalum hay (Paspalum dilatatum).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Based on the analysis of the design and operation of vertical-spindle cotton harvesting machines, as well as numerous studies aimed at improving their efficiency, it can be concluded that cotton fibers are not captured by the spindle surface during operation in the absence of compression force, even at high spindle activity [9,14,15]. Figure 1 shows the orientation schemes of vertical spindles towards cotton bolls using their active surfaces.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the analysis of the design and operation of vertical-spindle cotton harvesting machines, as well as numerous studies aimed at improving their efficiency, it can be concluded that cotton fibers are not captured by the spindle surface during operation in the absence of compression force, even at high spindle activity [9,14,15]. Figure 1 shows the orientation schemes of vertical spindles towards cotton bolls using their active surfaces.…”
Section: Methodsmentioning
confidence: 99%
“…To study the dimensions and shape of the guiding channel, we will use the "GeoGebra" program, which has now gained wide distribution in the field of mathematical modeling and is successfully applied to study technical systems and mechanisms [8][9][10][11][12]. The program allows accelerating the modeling of technical systems, visually observing the final result by varying the geometric dimensions of the system elements.…”
Section: Methodsmentioning
confidence: 99%